ANALYSIS OF THE EFFECTIVENESS OF LAND AND BUILDING TAX AND ITS CONTRIBUTION TO STATE REVENUE - Samrin, La Ode Muhammad Arfan; Hadisantoso, Erwin; Dewangga, Puspa; Saenong, Zainuddin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the effectiveness of Land and Building Tax (PBB) collection and its contribution to state revenues during the period from 2019 to 2023. The method employed is a descriptive quantitative approach, utilizing secondary data analysis derived from PBB revenue realization reports and State Budget (APBN) data. Effectiveness is measured by comparing PBB revenue realization with the target, while contributions are analyzed based on the proportion of PBB to total state revenues. The results show that PBB collection is highly effective, with an average effectiveness above 100% for five consecutive years. However, its contribution to state revenues is very low, ranging from only 0.89% to 1.29%. This finding suggests that, although PBB collection administration has been operating optimally, its fiscal potential has not been fully realized. This study recommends reforming the property tax system, including updating taxable object data, increasing public tax literacy, and digitizing the regional tax administration system, to significantly increase PBB's contribution to state revenues.